Index of Seagrass Ecology at Prawean Beach, Jepara - Anggi Rahmadani Kusumaningtyas; Suryono Suryono; Ambariyanto Ambariyanto (Journal of Marine Research, 2023)
Seagrass ecosystems are limited by several environmental factors, namely temperature, light, salinity, depth, primary substrate, nutrients and movement of seawater (waves, currents, tides). The type of substrate can cause differences in the composition of seagrass species and affect differences in the fertility and growth of each kind of seagrass. Seagrasses are suitable for living on muddy, sandy, loam, or substrates with coral fragments and rock crevices. This study aims to determine the ecological index of seagrass in Prawean Beach, Jepara. The research was conducted using an exploratory descriptive method. The study was carried out in November 2021. The materials used in this study were sediment and seagrass samples. The research was carried out in November 2021. Identification of seagrass species using the LIPI method and grain size analysis of sediments using the granulometric method. PCA analysis aims to determine the variables of ecological factors that affect the ecological index of seagrass. PCA analysis will show necessary information regarding the relationship between variables in one graph. The results obtained four seagrass types: Thalassia hemprichii, Enhalus acoroides, Cymodocea serrulata and Cymodocea rotundata. The species density value is classified as relatively dense and the species cover value is classified as less rich/unhealthy with the type of sediment in the form of fine sand. PCA analysis resulted in 3 main factors formed, namely: F1) Enhalus acoroides cover, gravel, silt, temperature, pH and current; F2) Sand and salinity; and F3) Density and cover of Cymodocea rotundata.